2022
DOI: 10.1039/d2qo00732k
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective electrophilic B(9)-amination of o-carborane driven by HOTf and HFIP

Abstract: Despite the great importance of nitrogen-containing carboranes in organic and pharmaceutical synthesis, current methods to generate them are very limited and usually rely on the use of expensive transition metals....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Based on our previous work on the electrophilic substitution reactions of o -carboranes in HFIP, , we conducted the reaction of o -carborane and 68% HNO 3 in HFIP (Table , entry 1). Unfortunately, initial attempts did not deliver any product.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous work on the electrophilic substitution reactions of o -carboranes in HFIP, , we conducted the reaction of o -carborane and 68% HNO 3 in HFIP (Table , entry 1). Unfortunately, initial attempts did not deliver any product.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous reports, , we initially examined the influence of Brønsted acids on the electrophilic chlorination of o -carborane under one equivalent halogenating agent TCCA in HFIP solvent (Table , entries 1–4). It was found that the addition of Brønsted acids could slightly promote the reaction, and the best result was obtained when HOTf was used.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous reports, 12,15 we initially examined the influence of Brønsted acids on the electrophilic chlorination of o-carborane under one equivalent halogenating agent TCCA in HFIP solvent (Table 1, entries 1−4 and the best result was obtained when HOTf was used. The yields of the desired product 9-Cl-o-carborane 1 increased significantly with the increase of HOTf (Table 1, entries 2, 5, and 6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations